Ko z raziskovanjem posegamo v družine - Urbančič, Klaudia (Obzornik zdravstvene nege, 2002)
Many fields of nursing is involved in the care for families. The article presents families from the point of research. The purpose of the article is topresent special features of research work in nursing care in cases families are involved The article also presents directives of the International Councilof Nurses, starting points of directions for research work within families, limitations of research work performed in families and basic requirements for research work process. Theoretical starting points are supported by the results of research performed on families in clinical settings. The supplement brings specific instructions for the application for the permission of the Ethical Commission in Slovenia.
Keywords: Družina; Family; Nursing Research; raziskave; zdravstvena nega; Zdravstvena nega, raziskava